Application of molecular biology techniques to the taxonomy and identification of Fusaria, particularly Fusarium Oxysporum F. Sp. Dianthi - Kotze, J.M. (University of Pretoria, 2022)
Thesis (DSc (Agric))--University of Pretoria, 1988.